NETWORK OF ACTORS IN THE CONTEXT OF SPECIAL PROTECTION FOR CHILDREN - Willya Achmad (Sean Institute, 2023)
This research aims to explore the role of various actors involved in specific protection efforts for children. Special protection of children is becoming increasingly important in the changing global social and political context. With a focus on the child protection framework, this research analyzes the contribution of various actors such as government, non-governmental organizations, communities and families in efforts to protect children from various forms of exploitation, violence and neglect. The research method used in this research involves a comprehensive literature survey and qualitative analysis of child protection policies and programs that have been implemented in Indonesia. The research results show that the active involvement of various actors, including the government, universities, school agencies, hospitals, police and courts, has an important role in implementing special child protection policies in Indonesia. The involvement of universities and school agencies in educational outreach activities provides significant education regarding child protection issues to students and teachers. Apart from that, the role of hospitals in providing comprehensive medical services, as well as the role of the Police and Courts in ensuring legal protection for victims of violence, has also proven important in handling cases of violence against children. Collaboration and solid coordination between all these actors proves that building an integrated network is essential in efforts to realize overall child protection policy goals.